2019
DOI: 10.14814/phy2.14253
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone fails to improve bleomycin‐induced acute lung injury in mice

Abstract: Acute respiratory distress syndrome (ARDS) features an exudative phase characterized by alveolar damage, lung edema and exacerbated inflammatory response. Given their anti‐inflammatory properties, the potential therapeutic effect of corticosteroids has been evaluated in ARDS clinical trials and experimental models of ALI. These studies produced contradictory results. Therefore, our aim was to investigate the effects of dexamethasone in an animal model of bleomycin‐induced acute lung injury and then to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 56 publications
3
17
0
Order By: Relevance
“…The first one was to evaluate the impact of a treatment with a corticosteroid (dexamethasone) on the resolution of bleomycin‐induced ALI (comparison between the control groups and mice treated with dexamethasone after the bleomycin challenge). These results have already been published (Aubin Vega et al., 2019). The second question was to explore the impact of αENaC down‐regulation (in αENaC(−/−)Tg+ mice) in the bleomycin‐induced ALI model (data presented here comparing the control and αENaC(−/−)Tg+ groups).…”
Section: Methodssupporting
confidence: 74%
See 2 more Smart Citations
“…The first one was to evaluate the impact of a treatment with a corticosteroid (dexamethasone) on the resolution of bleomycin‐induced ALI (comparison between the control groups and mice treated with dexamethasone after the bleomycin challenge). These results have already been published (Aubin Vega et al., 2019). The second question was to explore the impact of αENaC down‐regulation (in αENaC(−/−)Tg+ mice) in the bleomycin‐induced ALI model (data presented here comparing the control and αENaC(−/−)Tg+ groups).…”
Section: Methodssupporting
confidence: 74%
“…The second question was to explore the impact of αENaC down‐regulation (in αENaC(−/−)Tg+ mice) in the bleomycin‐induced ALI model (data presented here comparing the control and αENaC(−/−)Tg+ groups). Thus, in order to decrease the number of animals used as per the 3Rs principles, the same group of animals was used as control within the two studies performed at the same time and the values reported here (Ctl group) are similar to the ones recently published in (Aubin Vega et al., 2019).…”
Section: Methodssupporting
confidence: 55%
See 1 more Smart Citation
“…However, depletion of the main inflammatory cells such as neutrophils and inflammatory monocytes with an anti-Gr1 antibody does not affect fibrosis development [37,38]. Furthermore, administration of anti-inflammatory drugs like dexamethasone does not inhibit fibrosis development [23,39]. Therefore, inflammation itself may not be an essential component of fibrosis development, and studies on fibrosis-specific cascades are recognized as important for understanding the pathogenesis of fibrosis onset.…”
Section: Interaction Between Structured and Non-structured Cells In Tmentioning
confidence: 99%
“…Glucocorticoids are considered as fundamental choice of drugs for the prevention and treatment for such inflammatory adverse events 1 , 5 , 6 . However, the adverse side effects of glucocorticoids, including opportunistic infections 7 , osteonecrosis of femoral head 8 , and secondary diabetes 9 , makes their continued use in these cases more complicated 8 , 10 .…”
Section: Introductionmentioning
confidence: 99%